A label-free and enzyme-free fluorescent aptasensor for amplified detection of kanamycin in milk sample based on target-triggered catalytic hairpin assembly. (March 2022) - Cui, Wanling; Hu, Guodong; Lv, Enguang; Li, Chonghui; Wang, Zhenxing; Li, Qiang; Qian, Zhaohong; Wang, Jihua; Xu, Shicai; Wang, Rui
Abstract: Kanamycin residues in foods can cause serious adverse reactions in human body, and the accurate and sensitive detection of kanamycin is of great significance to ensure human health. In this work, we constructed a label-free and enzyme-free fluorescent aptasensor for quantifying kanamycin in milk based on target-triggered catalytic hairpin assembly. First, we designed an aptamer probe that contained an aptamer unit for recognizing kanamycin, a trigger unit for triggering catalytic hairpin assembly and a suppression unit for ensuring the stability of aptamer probe. In the initial state, the trigger unit was closed by suppression unit and inactive. After the aptamer unit recognized and bound to kanamycin, a free trigger unit was released to trigger the cycle hybridization reactions between hairpin probe 1 and hairpin probe 2, generating G-rich complexes and realizing enzyme-free amplification detection. Then, N -methylmesoporphyrin IX as signal molecules were combined with G-rich complexes to generate a significant fluorescent signal, which realized label-free detection. Thus, the aptasensor provided a well sensitivity for kanamycin with a detection limit of 0.26 ng/mL. And it possessed well selectivity and could distinguish kanamycin from its analogues, which stemmed from the specific recognition between kanamycin and aptamer. The aptasensor had great potential application value in the field of ensuring food safety. Graphical abstract: Image 1 Highlights: A sensitive fluorescent aptasensor for quantifying kanamycin was proposed. The aptasensor could realize label-free and enzyme-free detection of kanamycin. The aptasensor was based on target-triggered catalytic hairpin assembly. The detection limit was calculated to be 0.26 ng/mL for kanamycin. The aptasensor provided a potential tool for ensuring food safety.